Associating Technology Innovation Domains with Quality Service Performance of Public Health Care Organizations - Mohammed Hassan Abdulla, Ayesha Salem; Al-shami, Samer Ali (International Journal of Sustainable Construction Engineering and Technology, 2023)
This paper has presented the modelling of three technology innovation domains namely Organization Innovation Capabilities; Potential Absorptivity Knowledge; and Interaction with Technology affecting the UAE Health Care organisation performance construct. The modelling processes was conducted in SmartPLS software using 398 data gathered through questionnaire survey amongst employees of UAE public health care organization. Results from the modelling analysis found that model fitness criteria, which are Chi-Square value and NFI (Normed Fit Index) have an acceptable fit index. The model also has excellent predictive relevance for independent constructs that have fully account for the variance in dependent construct. however, one of the three paths was found not significant which is the path from OIC to OP. In term of path strength, paths from the construct OP to IWT has coefficient value of 0.3; to OIC has coefficient value of 0.1; and to PAK has coefficient value of 0.4. It is hope that the findings from this study have contributed to the knowledge of the relationship between the technology innovation dimension affecting the UAE public health care organization.